IMF Staff Papers, Volume 51, No. 2. (IMF Staff Papers; IMF Staff Papers ;, 2004)
This second issue for 2004 contains 8 new papers, including notable contributions from: Nancy Brune, Geoffrey Garrett, and Bruce Kogut on the global spread of privatization; and Mark P. Taylor and Elena T. Branson on asymmetric arbitrage and default premiums in the U.S. and Russian markets. Other papers in the issue look at German wage structures, contagion in equity markets, export orientation and productivity in Sub-Saharan Africa, the role of higher vs. basic education in economic development, and issues related to capital account liberalization.